Development and validation of the Guided Group Discussion Self-Estimate Inventory (GGD-SEI) - Martin, David; Campbell, Bill (British journal of guidance & counselling, 1998)
A 19-item self-report measure was designed to promote increased self-awareness of a group leader's perceived ability to facilitate guided small-group discussion. A factor analysis of responses from students about to embark on a micro-training course in guided group discussion(N = 154) yielded four factors that reflected subjects' belief in their ability to utilise specific group management skills. The scale had high internal reliability (a = 0.92). Initial validity estimates show that the instrument is (i) positively associated with an assessment of interpersonal skills, and (ii) minimally related to self-perceptions of locus of control, fear of negative evaluation, and estimates of self-esteem. The instrument, developed for use within education and training settings, provides a useful measure of guided small-group discussion self-efficacy.